The revival and revitalization of musical bow practice - Mandela, Thandile (College of Music, 2026)
In writing this Preface, I found myself constantly pausing to think on events which stimulated my interest in African musical bows. I grew up in a rural area in the Eastern Cape, historical home of the Xhosa-speaking people, and in which so much Xhosa traditional music has always been actively practiced. It seems hard to believe that musical bow performance never came into my social experiences. But this is because there were no active performers around me, or if there were, I was not aware of them, being concerned with the daily routine of growing up and going to school, and attending social events of the community and the church. It was only after I registered in the Honours progamme of the College of Music of the University of Cape Town, that I found myself among a handful of individuals who not only play musical bows, but have established reputations locally and abroad as African traditionalist musician, Dizu Plaatjies, his clan relative Madosini Manqineni, acknowledged 'Veteran' Xhosa musician, and professional colleague Mantombi Matotiyane. Through these individuals, and Dizu in particular, I was also introduced to a very wide range of African traditions from inside and beyond South Africa. You cannot imagine my astonishment when I first learned that the umrhubhe and uhadi bows were Xhosa cultural instruments, of my own musical heritage. I am deeply indebted to Dizu for opening up for me the rich treasury of our classical Xhosa music, but I am certain that even he could not really appreciate the depth of my ignorance of its principal sound instruments, and their socio-cultural meaning and value, just over three years ago. And when I had access to a CD release of Madosini's compositions, and to the amount of literature on Xhosa and other African music, my 'conversion' to African music was finally completed. Today my musical experiences are moving among many African musics, but they are strongly rooted in Xhosa musical culture.